Modeling and Analysis of Battery Thermal Control in a Geostationary Satellite - Nedim Sözbir; Murat Bulut (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Battery technology has been used for geostationary satellites since the first satellite sputnik-1 was launched in 1957. The majority of larger geostationary satellite’s lives range from 7 to 15 years. During the lifetime of satellites, the batteries used must complete 1000 to 33000 cycles without any problems or likelihood of maintenance. There are three battery technologies, Li-ion, Ni-H2 and Ni-Cd, that are well proven for Geostationary satellite applications. Energy density, lifetime, weight, ampere-hour capacity, depth of discharge, ruggedness and recharge-ability, battery management, thermal management, and self-discharge are main parameters that should be considered when comparing electrical and thermal performance of these three battery technologies. The purpose of this study is to compare the thermal control system for these three batteries for three-axis stabilized geostationary satellites. In particular, the thermal dissipation was compared, which is the temperature range required for battery operation. Thermal analysis was performed for Li-ion batteries using ThermXL software, and showed a temperature results variation ranging between 10.9 oC and 32.7 oC. The temperature during the battery module was not greater that its qualification temperature results.